Composite Micromechanical Analysis Learning Tool (CMALT) - Suhaime, Schufee Amani; Rosli, Fatin Rohaina; Ismail, Mohd Shahrom; Ab Patar, Mohd Nor Azmi; Mahmud, Jamaluddin (2025)
Micromechanical analysis is essential for predicting the effective stiffness of composite laminas based on fiber and matrix properties. However, the mathematical complexity of models such as the Rule of Mixtures, used to calculate longitudinal (E₁) and transverse (E₂) moduli, often presents difficulties for undergraduate learners. To address this educational gap, the Composite Micromechanical Analysis Learning Tool (CMALT) was developed as an interactive web-based platform aimed at enhancing understanding of composite behavior through real-time simulation. Built using Python and Streamlit, CMALT enables users to input the elastic moduli of constituent materials and fiber volume fraction to compute E₁ and E₂ using established micromechanical equations. The tool features dual case study comparisons, predefined material presets, graphical visualization, and immediate numerical output to support interactive exploration of composite configurations. Validation against analytical calculations showed complete agreement, confirming the tool’s computational accuracy. With its clean interface, browser-based accessibility, and integration of theoretical concepts with simulation, CMALT offers a practical solution for improving teaching and learning in composite mechanics. Future developments may include support for advanced micromechanical models, additional property calculations, and exportable results to further enhance its academic and research applications.